CH3O‐PEABr Passivated Quasi‐2D Perovskite BA2Cs4Pb5Br16 Thin Film for Green Light‐Emitting Diodes - Yuxin Liu; Lei Song; Xiaofei Zhang; Ang Bian; Chengxi Zhang; Jun Dai (Advanced Electronic Materials)
Abstract In this paper, the quasi‐2D green perovskite BA2Cs4Pb5Br16 film passivated by the CH3O‐PEABr is reported to realize nonradiative defect suppressing. The passivated BA2Cs4Pb5Br16 film has a large exciton binding energy (74.9 meV), which is conducive to efficient radiation recombination. Time‐resolved photoluminescence and ultrafast transient absorption spectroscopy show that the carrier lifetime is effectively prolonged after CH3O‐PEABr passivation, indicating photoluminescence enhancement is attributed to the nonradiative defect suppressing. Finally, an electroluminescent green light‐emitting diodes device is fabricated based on the CH3O‐PEABr‐passivated BA2Cs4Pb5Br16 thin film, the maximum external quantum efficiency can be 19.47%. The results indicate that the CH3O‐PEABr passivated BA2Cs4Pb5Br16 thin film can be a promising material for the high‐performance green light‐emitting diodes.